A Note on Cryptanalysis of the Preliminary Version of the NTRU Signature Scheme - Mironov, Ilya (2001)
In this paper a preliminary version of the NTRU signature scheme is cryptanalyzed. The attack exploits a correlation between some bits of a signature and coefficients of a secret random polynomial. The attack does not apply to the next version of the signature scheme.